Ancients and Honorables parade on State Street, June 1965 - Unknown (Tufts Archival Research Center, 2005)
Elevated-view east-northeast of the Ancients and Honorables parade on State Street. Clocks, billboards and signage adorn many of the buildings that line both the north-northwest and south-southeast sides of State Street. Street lights and pedestrians line the sidewalks along the street. 2 7/8 x 3 3/4, 3 3/8 x 4 1/4 overall Diffusion transfer prints